2021
DOI: 10.1002/cplu.202000767
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidative [2+2] Cycloelimination Reactions with Flavinium Salts: Mechanistic Study and Influence of the Catalyst Structure

Abstract: Dedicated to Professor František Liška on the occasion of his 80th birthday. Flavinium salts are frequently used in organocatalysis but their application in photoredox catalysis has not been systematically investigated to date. We synthesized a series of 5-ethyl-1,3dimethylalloxazinium salts with different substituents in the positions 7 and 8 and investigated their application in lightdependent oxidative cycloelimination of cyclobutanes. Detailed mechanistic investigations with a coumarin dimer as a model sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
1
6
1
Order By: Relevance
“…However, methoxy functionalities have a positive effect on the properties of the flavin photocatalyst causing its high stability, while maintaining its highly positive excited state reduction potential. A similar effect has already been described among the neutral alloxazines used in energy transfer cycloadditions, [28] 5‐ethylalloxazinium salts used in [2+2] cycloelimination, [29] and acridinium salts used in various photooxidative processes [30] . We plan to further investigate this effect among flavin derivatives and to evaluate the performance of stable and powerful salt 1 a in other photooxidative processes.…”
Section: Discussionsupporting
confidence: 63%
“…However, methoxy functionalities have a positive effect on the properties of the flavin photocatalyst causing its high stability, while maintaining its highly positive excited state reduction potential. A similar effect has already been described among the neutral alloxazines used in energy transfer cycloadditions, [28] 5‐ethylalloxazinium salts used in [2+2] cycloelimination, [29] and acridinium salts used in various photooxidative processes [30] . We plan to further investigate this effect among flavin derivatives and to evaluate the performance of stable and powerful salt 1 a in other photooxidative processes.…”
Section: Discussionsupporting
confidence: 63%
“…Whereas such processes have previously been observed in e.g. cycloreversion processes, 18 we were only able to observe a diastereoisomerization process instead of cycloreversion. This observation was only made after prolonged irradiation of the reaction mixture and highlights the complexity of photocatalytic reactions.…”
contrasting
confidence: 54%
“…Therefore, we concluded that the different product ratios correlate to a secondary reaction from the cyclobutane products by PET similar to a photocycloreversion reaction. 17,18 Additionally, the photolysis experiments were performed in different solvents, which will only be illustrated for the case of MeCN and toluene (see Tables S1-S3, ESI, † for additional information). From nonpolar solvents such as toluene, a general observation was a significantly preferred formation of the chalcone dimers, which may be attributed to an increased p-stacking interaction of the substrates and solvent molecules.…”
mentioning
confidence: 99%
“…Transient absorption data are analyzed by a global fit using an exponential ansatz, which is adequate for the description of the photophysics of a single chromophore in solution. The global fits were performed using an in-house written program described previously, e.g., in which the linear least-squares problem in eq is solved χ 2 = || Δ A boldF boldB || 2 = min …”
Section: Materials and Methodsmentioning
confidence: 99%